Association between monocyte-high density lipoprotein ratio (MHR) and severity level of lower extremity artery disease (LEAD) - . Faizin; Bambang Irawan; Hariadi Hariawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
The incidence of lower extremity artery disease (LEAD) has increased worldwide in the last decade. Its severity has been associated with increased morbidity and mortality. Atherosclerosis is believed as the main cause of LEAD. Monocytes and low-density lipoprotein (LDL) are the hallmarks of atherosclerosis. High-density lipoprotein (HDL) plays a role in suppressing the activation of monocytes. The monocyte to HDL ratio (MHR) has been reported as a marker of coronary artery disease complexity. However, this marker has not been investigated to assessthe LEAD severity. The study aimed to investigate the association between MHR and LEAD severity. This was an analytic observational study using a cross-sectional design. Patients were selected from the Vascular Disease Registry in Dr.Sardjito General Hospital, Yogyakarta from January 2016 – January 2019. The blood sample was drawn at one day prior, on the day, or one day after duplex ultrasound performed. The duplex ultrasound was then interpreted based on the duplex ultrasound score. Patients were classified into two groups according to the score i.e. severe (score ≥ 8) and nonsevere (score< 8). Where as, the MHR was classified into two groups according to the cut-off point i.e. high (≥ 14.51) and low (< 14.51). The Chi-square test was used for statistical analysis and pvalue <0.05 was considered as statistically significant. A total of 50 patients were involved in this study. There were 21 (42%) patients in the severe group and 29 (58%) in the nonsevere group. The proportion of the high MHR group and the low MHR group with severe levels of LEAD were 12 (57.1%) and 9 (42.9%), respectively. However, it was not statistically significant [p = 0.145; CI95% PR 1.57 (0.81 – 3.03)]. In conclusion, there is no association between MHR and LEAD severity.